2013
DOI: 10.1039/c3ra42154f
|View full text |Cite
|
Sign up to set email alerts
|

Non-specific clustering of histidine tagged green fluorescent protein mediated by surface interactions: the collective effect in the protein-adsorption behaviour

Abstract: The chemically programmed non-fouling surfaces were used to observe the surface assembly behaviour of hexahistidine tagged Green Fluorescent Protein (His-GFP) as a model protein. In this particular case, siteselective physisorption of His-GFP was achieved in the absence of metal ions. This preference does not arise from surface charge, wettability or topographic differences between regions. We found that His-GFP has a tendency to centre into an array of marked squares and acquires a template shape on the entir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Future lines of work derive from the assumptions of the model employed in this work. Expanding our calculations from 1D to 3D systems (that is, without considering lateral homogeneity as we have done in this work) would allow us to study clustering of proteins, the role of surface properties, and whether this process is surface-mediated [77]. We would like to explore how protein changes upon adsorption can alter the process.…”
Section: Discussionmentioning
confidence: 99%
“…Future lines of work derive from the assumptions of the model employed in this work. Expanding our calculations from 1D to 3D systems (that is, without considering lateral homogeneity as we have done in this work) would allow us to study clustering of proteins, the role of surface properties, and whether this process is surface-mediated [77]. We would like to explore how protein changes upon adsorption can alter the process.…”
Section: Discussionmentioning
confidence: 99%
“…13−15 In 2013, Sobiesćiak et alinvestigated the protein assemblies of His-tagged GFP proteins and found that the clustering of the proteins is a surface-mediated process, and that self-assembled monolayers (SAMs) can guide the formation of various protein arrays. 16 In 2017, Wasserberg et al examined the interaction between red fluorescence protein (RFP) tagged with histidines and Ni 2+ :nitrilotriacetic acid (NTA)-terminated thiols placed on an Au(111) slab. They discovered that the binding affinity increased with the length of the His tag, and the orientation could be precisely controlled by the careful placement of His tags.…”
Section: ■ Introductionmentioning
confidence: 99%